Reka Bentuk Dan Pembangunan Modul Biod Stem Animalia Peringkat Pra Universiti - Saad, Hidayatul Illah Ahmad (2022)
This study aims to develop learning modules based on the STEM integration approach (BioD STEM Animalia Module) in Biodiversity topics, identify learning module needs for Biology learning, design and develop modules and evaluate the applicability of the BioD STEM Animalia module in the pre-university level. The study was carried out in three phases. The objective of the first phase was to identify the need for the BioD STEM Animalia Module for the Biology learning module in pre-university. A needs analysis study through survey and qualitative methods was conducted on teachers who teach Biology subjects in pre-university. The objective of the second phase of this study was to design and develop the BioD STEM Animalia module for the Biology learning module in pre-university by using Delphi techniques in the design of the module. The objective of the third phase of this study is to examine the applicability of BioD STEM Animalia module for the Biology learning module in pre-university to study teachers' perceptions of the usability characteristics of the module and to study students' attitudes towards the applicability of BioD STEM Animalia module. This study is a Design and Development Research Approach referring to the ADDIE Module development model to develop modules. Descriptive and mean analysis were used to analyze the quantitative data and interview and document analysis methods were used to analyze the qualitative data to determine the need in the design of the BioD STEM Animalia module in pre-university.